2016
DOI: 10.1002/jobm.201600400
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term straw returning affectsNitrospira‐like nitrite oxidizing bacterial community in a rapeseed‐rice rotation soil

Abstract: Nitrospira are the most widespread and well known nitrite-oxidizing bacteria (NOB) and putatively key nitrite-oxidizers in acidic ecosystems. Nevertheless, their ecology in agriculture soils has not been well studied. To understand the impact of straw incorporation on soil Nitrospira-like bacterial community, a cloned library analysis of the nitrite oxidoreductase gene-nxrB was performed for a long-term rapeseed-rice rotation system. In this study, most members of the Nitrospira-like NOB in the paddy soils fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Of them, the soil pH had no significant changes over six years between the straw return and removal treated soils at both soil depths ( Table 1 ). It is consistent with the previous results [ 16 , 26 ], and means that straw return will not result in soil acidification. In addition, straw return improved the contents of TC, TN, available N, available K and SOC at both depths but the effects were not significant ( Table 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of them, the soil pH had no significant changes over six years between the straw return and removal treated soils at both soil depths ( Table 1 ). It is consistent with the previous results [ 16 , 26 ], and means that straw return will not result in soil acidification. In addition, straw return improved the contents of TC, TN, available N, available K and SOC at both depths but the effects were not significant ( Table 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Soil pH was measured with a soil to water ratio of 1:2.5 (W/V) using a pH meter [ 16 ]. Soil total carbon (TC) and total nitrogen (TN) contents were determined through dry combustion with ground samples (100 mesh) on vario PYRO cube element analyzer (Elementar Corporation, Hanau, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The previous study has demonstrated that members of Proteobacteria can utilise reduced sulphur compounds to obtain energy and also through carbon assimilation via the reductive tricarboxylic acid (rTCA) cycle 43 . Interestingly rare taxa <1% belong to Armatimonadetes, AC1, NC10, NKB19, OP8 and GN04 (Table S1) were detected in both the enrichments.…”
Section: Diversity Of Microbial Communitiesmentioning
confidence: 99%
“…They also found that soil depth (related to O 2 content) and sampling site (related to rice rhizosphere) affect Nitrobacter activities in paddy soils. Long-term straw applications selected several lineages II Nitrospira , which were probably affected by the increment of available soil potassium, NH 4 + and NO 3 - , as well as decrements of available phosphorus in paddy-upland soil ( Luo et al, 2017 ). Our previous study also showed that Nitrospira -like NOB community composition is more sensitive than Nitrobacter to land management in acid and straw application soils of a rapeseed-rice rotation field trial, and the abundance of Nitrospira was always greater than Nitrobacter ; Nitrospira was affected by the straw application, while Nitrobacter was not ( Han et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%